2014
DOI: 10.1007/s12035-014-8981-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-219 Protects Against Seizure in the Kainic Acid Model of Epilepsy

Abstract: Emerging evidence indicates that certain microRNAs (miRNAs) play important roles in epileptogenesis. MiR-219 is a brain-specific miRNA and has been shown to negatively regulate the function of N-methyl-D-aspartate (NMDA) receptors by targeting Ca(2+)/calmodulin-dependent protein kinase II (CaMKII)γ. Herein, we found that the level of miR-219 was decreased in both the kainic acid (KA)-induced epilepsy model and in cerebrospinal fluid specimens of epilepsy patients. Importantly, silencing of miR-219 by its antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
108
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 31 publications
6
108
1
Order By: Relevance
“…Consistent with previous studies [6,52,53], our findings indicate that M1 MG/MΦ polarization augments glutamate toxicity, which may lead to apoptosis (and/or other types of cell death) of pyramidal neurons and extensive gliosis, which in turn may underlie, at least in part, the potential occurrence of spontaneous seizures in the chronic phase.…”
Section: Mg/mφ Polarization Affects Se Through Glutamate-metabolism-rsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies [6,52,53], our findings indicate that M1 MG/MΦ polarization augments glutamate toxicity, which may lead to apoptosis (and/or other types of cell death) of pyramidal neurons and extensive gliosis, which in turn may underlie, at least in part, the potential occurrence of spontaneous seizures in the chronic phase.…”
Section: Mg/mφ Polarization Affects Se Through Glutamate-metabolism-rsupporting
confidence: 91%
“…NMDA receptors play critical roles in epileptic excitotoxicity, and NMDA receptor antagonists have been used to treat refractory seizures [49,50]. NMDA receptor subunit composition has been reported to be altered in epilepsy models [6,[41][42][43][44][45][46][47][48][49][50][51][52][53]. In addition, it has been reported that iNOS acts on mature neurons indirectly, increasing NMDA receptor expression [54].…”
Section: Mg/mφ Polarization Affects Se Through Glutamate-metabolism-rmentioning
confidence: 99%
“…As previously described [27], mice were subjected to miR-155 antagomir or NC injection into the right lateral cerebral ventricle (i.c.v., 0.5 mm posterior to the bregma, 1.0 mm lateral to the midsagittal suture, 2.2 mm below the dura matter) using a 10-μL Hamilton syringe at a speed of 0.3 μL/min in a stereotaxic instrument (RWD Life Science, Shenzhen, China). The syringe was held for 10 min after injection.…”
Section: Methodsmentioning
confidence: 99%
“…The EEGs of all mice were recorded for 2 h after the i.c.v. injection following the method described previously [27]. EEG data were analyzed by Nicolet 1.0 software in which the interference of alternating current was eliminated, and the sensitivity was uniformly adjusted to 20 μV/mm.…”
Section: Methodsmentioning
confidence: 99%
“…GWASs in east-Asian populations are limited; only one Japanese GWAS12 has been conducted. Although several studies in China have validated SNPs identified from GWASs in the western countries131415, no GWAS has been conducted in a Chinese population using microarray chips customized for Chinese populations. For LOAD, some genes have been consistently identified across GWASs, and these genes mainly belong to three biological pathways, i.e., the metabolic, trafficking, and signaling pathways161718.…”
mentioning
confidence: 99%